A comparative evaluation of marginal fit and microleakage of computer-aided design/computer-aided manufacturing-milled zirconia and prefabricated posterior occlusal veneers: An in vitrostudy - Vasundhra Bhati; Vikram Kapoor; Neeta Pasricha; Shrimant Raman; Pallavi Sirana (Wolters Kluwer Medknow Publications, 2024)
Aims: The aim of this study was to compare the marginal fit of prefabricated occlusal veneers with computer-aided design/computer-aided manufacturing (CAD-CAM)-milled zirconia occlusal veneers in the posterior teeth. Settings and Design: Forty extracted human maxillary premolars were divided into two groups of 20 each. Group 1 was prepared to receive prefabricated occlusal veneers, and Group 2 was prepared to receive CAD-CAM-milled zirconia occlusal veneers. Materials and Methods: Prefabricated samples (Edelweiss) were selected for Group 1, whereas for Group 2, the tooth preparations were scanned, and occlusal veneers were fabricated using Exocad designing software and milling machine. After luting, both the groups were submerged in dye, sectioned, and evaluated for marginal fit and microleakage under a stereomicroscope using the microscope imaging software and its measurement tool. Statistical Analysis Used: Data collected were subjected to statistical analysis using SPSS 27.0. Intragroup and intergroup comparison was done using the Mann-Whitney U test. The Chi-square test was applied to check the depth of penetration of dye based on percentages. Results: The marginal gap of zirconia occlusal veneers fabricated with CAD-CAM is higher compared to that of prefabricated occlusal veneers. Similarly, the depth of penetration of dye is higher in CAD-CAM-milled zirconia occlusal veneers than prefabricated occlusal veneers. Conclusion: The marginal fit of prefabricated occlusal veneer is better than the marginal fit of zirconia occlusal veneers fabricated with CAD-CAM. Similarly, it can also be concluded that the microleakage of prefabricated occlusal veneer is less compared to the CAD-CAM-milled zirconia occlusal veneers.